Interrelationship between liver hemodynamics and tumor metabolism in liver metastases: diagnostic value of Doppler perfusion index revisited - Alicioglu, B; Sarikaya, A; Bulakbasi, N (Prague medical report, 2013)
It should be expected that the hepatic blood flow increase in the cases with liver metastasis. We aimed to find out if there is a correlation between Doppler parameters and hepatic metabolic activity in oncology patients. 35 patients with hepatic metastases who were identified by 18F-fluorodeoxyglucose positron emission tomography scan and assessed with Doppler ultrasound were included in this prospective study. Patients with hepatic disease, cardiac dysfunction, dehydration, history of alcoholism, intake of antihypertensive or vasoactive medication were excluded. Volume flow of the proper hepatic artery and the portal vein were measured in the hepatoduodenal ligament by Doppler sonography. Doppler perfusion index (the ratio of the hepatic artery flow to the total liver blood flow) and flow volumes of 31 age matched subjects were compared. Both flow of the proper hepatic artery and portal vein were found to be significantly higher in patients with liver metastasis. The mean Doppler perfusion index value was 0.2 ± 0.13 in hepatic metastases whereas 0.13 ± 0.05 in control group. Doppler perfusion index was significantly higher in liver metastases (p=0.008). A positive correlation was found between the maximum standardized uptake value of the liver and flow volume of the proper hepatic artery (r=0.774, p=0). Blood flow of the proper hepatic artery and Doppler perfusion index correlates with hepatic standardized uptake value. Flow measurements of the liver may become an important parameter for selecting patients for further positron emission tomography scan and following-up the response after systemic and local therapeutic procedures.
Keywords: Hemodynamics; lidé; Middle Aged; Adult; Ultrasonography, Doppler; prospektivní studie; ultrasonografie dopplerovská; Female; Liver Neoplasms; Humans; Prospective Studies; regionální krevní průtok; lidé středního věku; mužské pohlaví; ženské pohlaví; hemodynamika; Regional Blood Flow; Male; Aged; dospělí; nádory jater; senioři